2015
DOI: 10.1051/0004-6361/201526044
|View full text |Cite
|
Sign up to set email alerts
|

Differential adsorption of CHON isomers at interstellar grain surfaces

Abstract: Context. The CHON generic chemical formula covers different isomers such as isocyanic acid (HNCO), cyanic acid (HOCN), fulminic acid (HCNO), and isofulminic acid (HONC); the first three have been identified in a large variety of environments in the interstellar medium (ISM). Several phenomena could be at the origin of the observed abundances, such as different pathways of formation and destruction involving gas phase reactions with different possible activation barriers and/or surface processes depending on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…for two substrates favouring the formation of OH bonds. A similar result, with the same origin, was obtained in a preceding study on the HCNO and HNCO couple of isomers whose attachments to the silica surface were found to be of ∼130 and 240 meV, whereas they are of ∼460 and 600 meV on the ice, respectively (Lattelais et al 2015). In any case, the different adsorption behaviour between HCN and HNC on naked grain surfaces or on water ice would likely induce different abundance ratios in different environments, which is well in line with their observed fluctuating abundance ratios in different regions of the ISM.…”
Section: Discussion and Final Remarkssupporting
confidence: 86%
See 1 more Smart Citation
“…for two substrates favouring the formation of OH bonds. A similar result, with the same origin, was obtained in a preceding study on the HCNO and HNCO couple of isomers whose attachments to the silica surface were found to be of ∼130 and 240 meV, whereas they are of ∼460 and 600 meV on the ice, respectively (Lattelais et al 2015). In any case, the different adsorption behaviour between HCN and HNC on naked grain surfaces or on water ice would likely induce different abundance ratios in different environments, which is well in line with their observed fluctuating abundance ratios in different regions of the ISM.…”
Section: Discussion and Final Remarkssupporting
confidence: 86%
“…As periodic calculations were based on the replication of the unit cell along the three directions of space, the size of the unit cell is a critical parameter whose dimensions were determined here to avoid any spurious lateral and vertical interactions between successive slabs. The experience drawn from preceding studies (Lattelais et al 2011(Lattelais et al , 2015 showed that a distance of ∼14 Å between the adsorbed species is necessary to avoid the interactions generated by lateral translations. The energy minima were then obtained by full optimizations starting from most of the chemically reasonable positions (over atoms and depressions) and orientations of the adsorbates over the host surfaces.…”
Section: Theoretical Approach To Adsorption Energiesmentioning
confidence: 99%
“…To avoid these limiting factors, a solution is to set up the icy environment with a proper solid surface of infinite dimension. Based on our preceding works on molecular adsorption on water ices (Lattelais et al 2011(Lattelais et al , 2015Bertin et al 2017), we took a periodic representation of solid hexagonal ice I h , composed of bilayers of water molecules. The ice surface was described by the (0001) Miller indices.…”
Section: Solid-state Approachmentioning
confidence: 99%
“…To address this issue, Mousis et al (2016b) investigated the question of the stability of the radiolytically produced O 2 molecules in the water matrix of ice grains. To do so, a sampling of the representative structures of O 2 in solid water ice has been obtained using a strategy based on first principle periodic density functional theory quantum calculations (Lattelais et al 2011(Lattelais et al , 2015Ellinger et al 2015). These calculations, performed in the case of hexagonal ice Ih using the Vienna ab initio simulation package (VASP) Hafner 1993, 1994), show that when 2, 3, or 4 adjacent H 2 O molecules were removed from the hexagonal lattice, well defined cavities form with shapes depending on the positions of the dismissed entities.…”
Section: Exogenic Radiolysis and O 2 Trapping In Icymentioning
confidence: 99%